HUNGARY IN THE EUROPEAN UNION: THE FIRST DECADE (2004-2014) - I. V. Kryuchkov (Современная наука и инновации, 2022)
The results of residence of Hungary in the European Union from 2004 to 2014 are considered in the article. The serious changes in national economy of the country, especially in industry, with the active participation of foreign capital are marked in the article. Hungary achieved the greatest success in the development of mechanical engineering, other knowledge-intensive branches of industrial production, services sector and tourism. The difficulties of adaptationof Hungarian economy to new conditions that led to significant social outgoings are emphasized in the material.The crisis phenomena appeared in agriculture and traditional sectors of industry of the country (food, textile, metallurgy, mining). The author comes to conclusion that the victory of «FIDESZ» party on parliamentary elections in 2010 and the forming of new economic strategy by the Prime Minister V. Orban are predictable. These processes are mainly connected with the growth of dissatisfaction of Hungarians with a traditional liberal model of socio-economic development of Hungary at the end of the XX - at the beginning of the XXI centuries.